Thiol-yne ‘click’/coupling chemistry and recent applications in polymer and materials synthesis and modification - Lowe, Andrew (Elsevier Ltd, 2014)
This review highlights recent applications of the thiol-yne reaction in polymer synthesis and modification and also gives some representative examples of its application in small molecule (bio)organic chemistry. A brief introduction to the history of the thiol-yne reaction is given followed by a description of the mechanism for the common radical-mediated manifestation of the reaction. This is followed by a review of its use in network/gel syntheses and modification, as a tool for polymer synthesis and copolymer modification; its applicability in the preparation of dendrimers and hyperbranched polymers and finally how it has been employed as a tool for surface modification and functionalisation. This review is not intended to be exhaustive but rather to serve as an overview of research areas within which this important reaction is currently attracting interest.